Pengaruh Inovasi Produk Dan Harga Terhadap Keputusan Pembelian Koleksi Jims Honey Pada Generasi Z Di Jakarta Timur - Wisinta Jusi Manurung; Tri Waluyo Prehantio (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This research aimed to analyze the influence of product innovation and price on the purchasing decisions of Generation Z in East Jakarta regarding Jims Honey products. This research was descriptive correlational with a quantitative approach. The sample consisted of 100 respondents from Generation Z consumers in East Jakarta, which was determined by the non-probability sampling method, namely purposive sampling, calculated using the Lemeshow formula. The research instrument was a questionnaire consisting of 30 statements with a fivepoint Likert scale. Data analysis included descriptive statistics, instrument testing (validity and reliability), classical assumption testing (normality, multicollinearity, and heteroskedasticity), multiple linear regression, and hypothesis testing (t-test, F-test, and coefficient of determination). Data processing was carried out using SPSS version 25. The results showed that product innovation had a positive and significant influence on purchasing decisions, price had a positive but insignificant influence on purchasing decisions, and simultaneously, product innovation and price both influenced purchasing decisions by 20.9%, with the remaining 79.1% influenced by other variables not examined in this research. Keywords: Product Innovation, Price, and Purchase Decision